Curriculum Relevance, Stakeholder Engagement, and Graduate Employability in Islamic Higher Education: Evidence from the KPI Graduate Program - Kamaruzzaman Kamaruzzaman; Linur Ficca Agustina; Muhammad Saleh; Harjoni Desky (Itqan: Jurnal Ilmu-ilmu Kependidikan, 2026)
Curriculum relevance has become a key indicator of higher education quality because it determines how well graduate competencies respond to workforce demands and stakeholder expectations. This study aims to assess the relevance of the Postgraduate Program in Islamic Communication and Broadcasting (KPI) curriculum at IAIN Lhokseumawe from the perspectives of alumni and institutional stakeholders. A qualitative descriptive approach was employed, involving twelve alumni and representatives from government institutions, schools, media organizations, communication agencies, and zakat institutions. Data were collected through semi-structured interviews, questionnaires, observations, and document analysis, and analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings indicate that the curriculum remains relevant in fostering ethical awareness, interpersonal communication, collaboration, and community engagement. However, competencies related to analytical thinking, strategic communication, digital literacy, policy analysis, and continuous professional development require further strengthening to meet evolving labour market demands. Stakeholders emphasized the importance of closer collaboration between universities and professional sectors to ensure continuous curriculum improvement. Based on these findings, this study proposes a Transformative Curriculum Framework integrating labour market foresight, competency-based curriculum, experiential learning, Islamic values and local wisdom, and sustainable stakeholder partnerships. The framework provides a context-sensitive model for strengthening curriculum relevance, graduate employability, and stakeholder value within Islamic higher education.